PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PEMBUATAN BUSANA INDUSTRI PADA KELAS XI TBS 1 TAHUN PELAJARAN 2019/2020 - Fenny Marlinda (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
This Classroom Action Research was carried out in the form of applying the Guided Discovery learning model to the lesson on Making Industrial Clothing in Class XI TB1 in the 2019/2020 Academic Year. The purposes of this classroom action research are 1) Knowing the application of the guided discovery learning model will improve the skills of Making Industrial Clothing in class XI TB1 in the 2019/2020 academic year. 2) Knowing how the application of the guided discovery learning model will improve Industrial Clothing Making Skills in class XI TBS1 for the 2019/2020 academic year. This research was carried out in two cycles where each cycle consisted of implementation planning, observation and reflection. The subjects of the research were the participants of Class XI TBS 1 Fashion Design. The data collection techniques were test and non-test techniques. While the data analysis uses quantitative and qualitative data analysis. The results of the action research show that there is a good indication of a change in Industrial Clothing Making skills, that is, classically, Industrial Clothing Making skills are 80%. At the end of cycle II the change in student skills was very good. Conclusion In this study learning by applying the guided discovery model has a positive impact on student learning outcomes, which is indicated by the large percentage of learning outcomes on average. The application of learning with the guided discovery model provides a pleasant learning atmosphere because students indirectly discover their own concepts so that they pay more attention to learning and result in students being more diligent, diligent, neat and disciplined in learning and ultimately improving learning outcomes.